Efficacy of Artilysin Art-175 against Resistant and Persistent Acinetobacter baumannii - Defraine, Valerie; Schuermans, Joris; Grymonprez, Barbara; Govers, Sander K.; Aertsen, Abram; Fauvart, Maarten; Michiels, Jan; Lavigne, Rob; Briers, Yves (Antimicrobial agents and chemotherapy, 2016)
Bacteriophage-encoded endolysins have shown promise as a novel class of antibacterials with a unique mode of action, i.e., peptidoglycan degradation. However, Gram-negative pathogens are generally not susceptible due to their protective outer membrane. Artilysins overcome this barrier. Artilysins are optimized, engineered fusions of selected endolysins with specific outer membrane-destabilizing peptides. Artilysin Art-175 comprises a modified variant of endolysin KZ144 with an N-terminal fusion to SMAP-29. Previously, we have shown the high susceptibility of Pseudomonas aeruginosa to Art-175. Here, we report that Art-175 is highly bactericidal against stationary-phase cells of multidrug-resistant Acinetobacter baumannii , even resulting in a complete elimination of large inocula (≥10 8 CFU/ml). Besides actively dividing cells, Art-175 also kills persisters. Instantaneous killing of A. baumannii upon contact with Art-175 could be visualized after immobilization of the bacteria in a microfluidic flow cell. Effective killing of a cell takes place through osmotic lysis after peptidoglycan degradation. The killing rate is enhanced by the addition of 0.5 mM EDTA. No development of resistance to Art-175 under selection pressure and no cross-resistance with existing resistance mechanisms could be observed. In conclusion, Art-175 represents a highly active Artilysin against both A. baumannii and P. aeruginosa , two of the most life-threatening pathogens of the order Pseudomonadales .